2014
DOI: 10.1021/jp5081862
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Stability of C6H3+Isomers

Abstract: The stability of the five main isomers of C6H3(+) was investigated using quantum chemical calculations. The cyclic isomers are stabilized by two complementary aromatic effects, first 6-electron π aromaticity, and second a more unusual three-center two-electron σ aromaticity. Two cyclic isomers sit at the bottom of the potential energy surface with energies very close to each other, with a third cyclic isomer slightly higher. The reaction barriers for the interconversion of these isomers, as well as to convert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Direct H-loss from phenylium involves a simple C-H bond breaking requiring 5.09 eV. This value is slightly higher (0.2 eV) than obtained at the CCSD(T) level, 22 which is likely due to the multi-configuration character of the m-benzyne C 6 H 4 + cation. 61 Ring opening-leading to the chain-like intermediate int2-can occur along two different reaction paths.…”
Section: Fragmentation Chemistrymentioning
confidence: 65%
See 2 more Smart Citations
“…Direct H-loss from phenylium involves a simple C-H bond breaking requiring 5.09 eV. This value is slightly higher (0.2 eV) than obtained at the CCSD(T) level, 22 which is likely due to the multi-configuration character of the m-benzyne C 6 H 4 + cation. 61 Ring opening-leading to the chain-like intermediate int2-can occur along two different reaction paths.…”
Section: Fragmentation Chemistrymentioning
confidence: 65%
“…25 Whereas there exists a general agreement that the 1 A 1 state is the ground state, the energy difference between the triplet and singlet states is somewhat uncertain, with calculations covering a range from 77 to 137 kJ mol À1 . [22][23][24]26,27 Photoelectron spectroscopy of the phenyl radical did not shed any light on the singlet-triplet (S-T) gap. 28 Some experimental support of a singlet ground state was offered in 2000, when a matrix-isolated IR spectroscopy study of phenylium reported vibrational frequencies at 713 and 3110 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that 1 is the global minimum structure for the C 6 H 3 + combination (at the CCSD(T)-F12b/cc-pVTZ + ZPE(B3LYP/cc-pVTZ)//CCSD(T)/cc-pVTZ level). 68 Thus, in the light of our current density analysis, it is possible to suggest that the high s and p aromatic character must be contributing to ring shaped stabilization of C 6 H 3 + . Whereas system 4, despite its substantial s-diatropic character, is not an energetically competitive isomer.…”
Section: Resultsmentioning
confidence: 73%
“…Some of them focus on the orbital‐optimization (OO) approach [ 10 ] to correct an artificial spin‐symmetry breaking occurring in spin‐unrestricted systems. [ 11–13 ] Others are based on the range‐separation exchange (RSX) scheme [ 14 ] to (partially) cure the self‐interaction and delocalization errors [ 15 ] (SIE and DE, respectively). [ 16–19 ] However, all of them conserve similar features, that is, a fraction of EXX generally larger than 50% and a fraction of PT2 correlation ranging between 10% and 40%, which allow them to reach the chemical accuracy when modeling a large panel of properties ranging from ground‐state energies [ 20 ] to structures [ 21,22 ] and extending to singlet‐singlet vertical excitation energies.…”
Section: Introductionmentioning
confidence: 99%